2014
DOI: 10.1002/chem.201303826
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Hoveyda–Grubbs Metathesis Catalysts Bearing S‐, Br‐, I‐, and N‐coordinating Naphthalene Ligands

Abstract: Derivatives of the Hoveyda-Grubbs complex bearing S-, Br-, I-, and N-coordinating naphthalene ligands were synthesized and characterized with NMR and X-ray studies. Depending on the arrangement of the coordinating sites on the naphthalene core, the isomeric catalysts differ in activity in model metathesis reactions. In particular, complexes with the RuCH bond adjacent to the second aromatic ring of the ligand suffer from difficulties experienced on their preparation and initiation. The behavior most probably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 59 publications
(103 reference statements)
5
25
0
Order By: Relevance
“…A similar, but more pronounced deactivating effect was found in the related derivative bearing the nitro group in ortho position to the iodine atom [17]. Further mechanistic studies using NMR spin-exchange spectroscopy at 80°C confirmed the occurrence of the anticipated fast cis-/transdichloro equilibrium and allowed for the determination of the position of the equilibrium under these conditions [18]. A correlation of the share of the trans-dichloro isomers in the equilibrium with the catalytic activity of the complexes led to the formulation of two general statements: (1) bromo-chelating compounds display a higher content of the trans-dichloro isomers going along with a higher catalytic activities (compared to analogous iodo-chelating complexes); and (2) effects of electronic tuning remain partially unclear-e.g., the content of the trans isomer increases for the NO 2 derivatives, while the catalytic activity decreases.…”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…A similar, but more pronounced deactivating effect was found in the related derivative bearing the nitro group in ortho position to the iodine atom [17]. Further mechanistic studies using NMR spin-exchange spectroscopy at 80°C confirmed the occurrence of the anticipated fast cis-/transdichloro equilibrium and allowed for the determination of the position of the equilibrium under these conditions [18]. A correlation of the share of the trans-dichloro isomers in the equilibrium with the catalytic activity of the complexes led to the formulation of two general statements: (1) bromo-chelating compounds display a higher content of the trans-dichloro isomers going along with a higher catalytic activities (compared to analogous iodo-chelating complexes); and (2) effects of electronic tuning remain partially unclear-e.g., the content of the trans isomer increases for the NO 2 derivatives, while the catalytic activity decreases.…”
Section: Introductionsupporting
confidence: 57%
“…Based on the experimental determination of the trans isomers content of pre-initiators 1-8 at 80°C in CDCl 3 performed previously [18], data are listed in Table 2, the shares of the trans forms in toluene at 80°C and in dichloromethane at 25°C were estimated. Although these estimations have to be taken with precautions (cf.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations